2020
DOI: 10.1186/s12941-020-00384-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2/COVID-19 and advances in developing potential therapeutics and vaccines to counter this emerging pandemic

Abstract: A novel coronavirus (SARS-CoV-2), causing an emerging coronavirus disease (COVID-19), first detected in Wuhan City, Hubei Province, China, which has taken a catastrophic turn with high toll rates in China and subsequently spreading across the globe. The rapid spread of this virus to more than 210 countries while affecting more than 25 million people and causing more than 843,000 human deaths, it has resulted in a pandemic situation in the world. The SARS-CoV-2 virus belongs to the genus Betacoronavirus, like M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 217 publications
(294 reference statements)
1
82
0
5
Order By: Relevance
“…Data showed that the ChAdOx1 nCoV-19 vaccine exhibited an appropriate safety profile and improved antibody and cellular immune responses. These findings endorse a large-scale assessment of this candidate vaccine in the ongoing phase 3 trial program ( 120 ).…”
Section: Control and Prevention Of Sars-cov-2supporting
confidence: 73%
See 1 more Smart Citation
“…Data showed that the ChAdOx1 nCoV-19 vaccine exhibited an appropriate safety profile and improved antibody and cellular immune responses. These findings endorse a large-scale assessment of this candidate vaccine in the ongoing phase 3 trial program ( 120 ).…”
Section: Control and Prevention Of Sars-cov-2supporting
confidence: 73%
“…A total of 167 vaccine candidates are being tested worldwide. Among these, 29 are under clinical observation and 138 are under preclinical trials until 13 August 2020 ( 120 ). The first vaccine against COVID-19 was developed and approved for use only by the Chinese army ( 27 ).…”
Section: Control and Prevention Of Sars-cov-2mentioning
confidence: 99%
“…Recently, several mAbs against viruses have been developed, including SARS-CoV-1 and MERS-CoV, in which the S protein is the major target described both in vitro and in vivo. According to some studies, the specific nAbs against SARS-CoV-1 RBD in the S protein could effectively block SARS-CoV-2 entry (218,225). However, Wrapp et al (226) tested several published SARS-CoV-1 RBD-specific nAbs and found that they do not have substantial binding to the S protein of SARS-CoV-2, suggesting that the cross-reactivity may be limited.…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…However, immunotherapy is effective and of immediate use, being of short duration. This approach also presented limitations, such as the possibility of abnormal reactions and other serious risks, such as induction of severe acute lung injury or ADE (225). Although we are living through a unique moment in science, with some mismatched information and novel, important discoveries being made every day, immunotherapy seems to be a possibly effective option to help patients until an effective, safe vaccine or treatment is developed.…”
Section: Immune Cell-based Therapymentioning
confidence: 99%
“…This increased risk may be related to the low-grade inflammation that characterizes these chronic diseases, age-related reductions in anti-viral immunity, expression of ACE2 in vulnerable tissues (e.g., adipose, heart), underlying tissue fibrosis, impairments in lung function, and non-medical factors (e.g., poverty, crowding). For more information on other aspects of SARS-CoV-2 and the COVID-19 pandemic, including aspects of viral epidemiology and evolution, disease pathogenesis, prevention and treatment, please refer to comprehensive reviews ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%